Solomon Rapids, Mitchell County - Thiessen, Laura (Kansas State University, The Chapman Center for Rural Studies, 2012)
In this paper you will see how twin town rivalry can lead to the death of a town. This will be done using the case study of Solomon Rapids located in Mitchell County Kansas. This study includes recent photographs of the Solomon Rapids town site.
Laura Thiessen, “Solomon Rapids, Mitchell County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/85.
Keywords: Mitchell County; Solomon Rapids; School District #11; C.J. Brown; Kansa Indians; Willow Springs